Preparation, primary structure and antifreeze activity of antifreeze peptides from Scomberomorus niphonius skin. (March 2019) - Fu, Weiqing; Wang, Peixin; Chen, Yueyu; Lin, Jiaxin; Zheng, Baodong; Zeng, Hongliang; Zhang, Yi
Abstract: In order to evaluate antifreeze activity of antifreeze peptides (AFPs) from Scomberomorus niphonius skin and study the relationship between antifreeze activity and primary structure, peptides were prepared and thermal hysteresis activity (THA), recrystallisation inhibition, molecular weight, and amino acid composition were investigated. Based on the results, alkaline protease was selected to prepare AFPs, and optimal hydrolysis conditions consisted of an enzyme-to-substrate (E/S) ratio of 1/50, pH 8.5, a temperature of 37 °C, and a time of 2 h. Under these conditions, the peptide content reached 39 mg/mL. At the optimal hold temperature of −0.1 °C, the THA of AFPs was 1.7 °C. AFPs significantly reduced the volume of ice crystals. The molecular weight of AFPs ranged from 1426 to 1810 Da. Glycine, alanine, and proline were the most abundant amino acids, and the primary structure was closely correlated with antifreeze activity. The findings suggested these antifreeze peptides have potential as additives in the food industry. Highlights: THA of AFPs from S. niphonius reach 1.7 °C, which are classified as "hyperactive". AFPs from S. niphonius significantly reduced the volume of ice crystals. AFPs from S. niphonius are likely to have the functional structure of (-Gly-Z-X-)n.